Two adjoint-based optimization approaches for a free surface Stokes flow - Repke, Sabine; Marheineke, Nicole; Pinnau, René (SIAM Journal on Applied Mathematics, 2011)
This work deals with the optimal control of a fre e surface Stokes flow which responds to an applied outer pressure. Typical applications are fiber spinning or thin film manufacturing. We present and discuss two adjoint-based optimization approaches that differ in the treatment of the free boundary as either a state or control variable. In both cases the free boundary is modeled as the graph of a function. The PDE-constrained optimization problems are numerically solved by the Broyden-Fletcher-Goldfarb-Shanno (BFGS) method, where the gradient of the reduced cost function is expressed in terms of adjoint variables. Numerical results for both strategies are finally compared with respect to accuracy and efficiency. © 2011 Society for Industrial and Applied Mathematics.
Keywords: Film casting process; Free surface stokes flow; Lagrange formalism; Optimal control; Thin films